2016
DOI: 10.1186/s12859-016-1233-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of housekeeping and tissue-specific driver nodes in human protein interaction networks

Abstract: BackgroundSeveral recent studies have used the Minimum Dominating Set (MDS) model to identify driver nodes, which provide the control of the underlying networks, in protein interaction networks. There may exist multiple MDS configurations in a given network, thus it is difficult to determine which one represents the real set of driver nodes. Because these previous studies only focus on static networks and ignore the contextual information on particular tissues, their findings could be insufficient or even be m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 86 publications
(135 reference statements)
0
11
0
Order By: Relevance
“…The aim is to identify the minimum number of inputs, termed ‘driver’ nodes, that can steer the system from any initial state to any final state in finite time. Past studies of network controllability have identified the driver proteins to be associated with human diseases like cancer 2226 and other molecular interaction networks 2730 .…”
Section: Introductionmentioning
confidence: 99%
“…The aim is to identify the minimum number of inputs, termed ‘driver’ nodes, that can steer the system from any initial state to any final state in finite time. Past studies of network controllability have identified the driver proteins to be associated with human diseases like cancer 2226 and other molecular interaction networks 2730 .…”
Section: Introductionmentioning
confidence: 99%
“…The important role of MD-nodes in network control is recognized both in theory (Nacher and Akutsu, 2012) and in various real-world networks (Nacher and Akutsu, 2013, Wan et al., 2002, Wuchty, 2014). In particular, the concept of MDSet has recently been adopted to analyze various biological networks, and the results showed that MD-nodes not only occupy strategic locations to control the networks but are also associated with various biological functions (Nacher and Akutsu, 2013, Nacher and Akutsu, 2016, Sun, 2015, Wakai et al., 2017, Wuchty, 2014, Zhang et al., 2016). Thus, we postulated that the composition of MD-nodes in a network represents its hidden control architecture.…”
Section: Introductionmentioning
confidence: 99%
“…While the SMGs in our PPINs tended to be high-degree nodes, only a small number of their interactions exhibited frequent disruptions (in agreement with previous reports 28 ), unlike the case for many other genes of a similar degree whose interactions were often perturbed. One possible explanation for this is that a majority of the randomly selected genes were house-keeping genes occupying more central positions in the PPINs 29 and thus highly prone to rewiring as detailed by Kim et al 30 . Also, this can mean that SMGs have subtle effects on the PPIN and affect the same interaction partner consistently across patients.…”
Section: Resultsmentioning
confidence: 99%